Effect of Film Position on the Flow and Heat Transfer Characteristics of Full-Ribbed Rotor Tip - Zhou, Haimeng; Wang, Chenglong; Kong, Zhiqi; Du, Wei; Wang, Zhongqi (Frontiers in Energy Research, 2022)
This article numerically studied the flow and heat transfer characteristics of the full-ribbed fluted tip of a rotor with four types of distribution of cooling films, namely, the mid-arc uniform film at the bottom of the groove, the uniform film on full perimeter ribs, the uniform film on the suction-side rib, and the uniform film on the pressure-side rib. The evolution of secondary flow in the tip clearance under these four conditions was discussed, and the effect of cooling film position on the tip leakage flow and tip heat transfer was also studied. The results showed that films in the ribs were more conducive to lower leakage flow rates and can reduce total energy losses. Adding cooling films on the single-side rib had a better effect on the control of leakage flow rate, with the most significant improvement due to adding cooling films on the suction-side rib. The mid-arc jet at the bottom of the groove can greatly contain the swirl structure in the groove, but it weakened the air sealing effect, which led to a rise in leak flow. The main reason for the swirl structure in the groove was that the leakage flow from the tip of the rotor was blocked by the cold air jet from the cooling films to form a backflow. The vortex inside the groove was the most violent when the air film hole was set on the pressure side, so the loss coefficient was higher, while the vortex inside the groove was the simplest when the cooling film hole was set on the suction side, and the energy loss caused by the vortex inside the groove was the least, and this structure was more favorable to the cooling of the leaf tip. It was also found that the uniformity of the outlet airflow angle distribution improved in the presence of cold air injection on the tip of the rotor.